Kinase‐Kernel Models: Accurate Chemogenomic Method for the Entire Human Kinome. Issue 11 (13th December 2013) - Tian, Li; Mukherjee, Prasenjit; Martin, Eric
Abstract Chemogenomic kinase‐kernel virtual screening models interpolate between very accurate, empirically‐trained Profile‐QSAR models of the nearest binding‐site homologues with IC50 assay data. Between them, activity has been predicted for the entire human kinome.